2013
DOI: 10.1073/pnas.1222264110
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Toso in activation of monocytes, macrophages, and granulocytes

Abstract: Rapid activation of immune responses is necessary for antibacterial defense, but excessive immune activation can result in life-threatening septic shock. Understanding how these processes are balanced may provide novel therapeutic potential in treating inflammatory disease. Fc receptors are crucial for innate immune activation. However, the role of the putative Fc receptor for IgM, known as Toso/Faim3, has to this point been unclear. In this study, we generated Toso-deficient mice and used them to uncover a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 35 publications
1
78
0
Order By: Relevance
“…The FcμR expression began at the early immature B cell stage in bone marrow and continued through to plasmablast stage of differentiation, accompanied by transient down-modulation during GC reactions 6 . Contrary to this, Lang et al recently reported that Ly6G + bone marrow granulocytes and Mφs expressed FcμR at extremely low density on their cell surface 57 . Strangely, Ly6G - bone marrow cells which should contain a significant number of FcμR-expressing B cells, were negative with their B68 mAb 57 .…”
Section: Potential Functionsmentioning
confidence: 84%
See 3 more Smart Citations
“…The FcμR expression began at the early immature B cell stage in bone marrow and continued through to plasmablast stage of differentiation, accompanied by transient down-modulation during GC reactions 6 . Contrary to this, Lang et al recently reported that Ly6G + bone marrow granulocytes and Mφs expressed FcμR at extremely low density on their cell surface 57 . Strangely, Ly6G - bone marrow cells which should contain a significant number of FcμR-expressing B cells, were negative with their B68 mAb 57 .…”
Section: Potential Functionsmentioning
confidence: 84%
“…Contrary to this, Lang et al recently reported that Ly6G + bone marrow granulocytes and Mφs expressed FcμR at extremely low density on their cell surface 57 . Strangely, Ly6G - bone marrow cells which should contain a significant number of FcμR-expressing B cells, were negative with their B68 mAb 57 . In this regard, we reexamined extensively and found that none of our mAbs reacted specifically with the cell surface of these phagocytes and that FcμR transcripts were clearly detectable in B-lineage cells but not in the double sorted Ly6G + granulocytes or in Rag1 -deficient splenocytes, which were devoid of B and T cells but contained abundant granulocytes and Mφs, even after 35 cycles of amplification 6, 58 .…”
Section: Potential Functionsmentioning
confidence: 84%
See 2 more Smart Citations
“…The Journal of Immunology, 2015, 194: 4055-4057. Two laboratories (Ohno and Mak) had generated Fcmr/ Toso-deficient mice, and from 2012 to 2015 four groups of investigators independently characterized their phenotypes (11)(12)(13)(14)(15)(16)(17)(18)(19). Clear differences in the reported phenotypes, in addition to the cellular distribution of FcmR/Toso, were evident but are not discussed in this article because they are not directly related to the topic of this meeting.…”
Section: Nomenclature Of Toso Fas Apoptosis Inhibitory Molecule 3 Amentioning
confidence: 99%